VD_FINDINFO Jug / 2015 / 164 vom 26. Mai 2015 - VD Tribunal cantonal (2015)
CONTRAT D'ENTREPRISE, PRIX EFFECTIF, AVIS DES DÉFAUTS, FARDEAU DE LA PREUVE, HYPOTHÈQUE LÉGALE, PLUS-VALUE | 837 al. 1 ch. 3 CC, 363 CO, 368 CO, 374 CO